Plastic materials and molded articles obtained therefrom
By adding less than 7.0% of metal element inorganic particles to the plastic material and controlling the material thickness, the problem of poor transmission of electromagnetic waves in the frequency range of 76GHz to 81GHz in the prior art is solved, and the effect of efficient transmission and low attenuation is achieved.
Patent Information
- Application Number
- JP2024558313
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-04-19
- Publication Date
- 2025-04-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to develop plastic materials that can effectively transmit electromagnetic waves in the frequency range of 76 GHz to 81 GHz, especially in external components of vehicles used to cover radar detection systems, where fluctuation attenuation problems exist.
Use plastic materials containing inorganic particles of less than 7.0% metal elements to ensure that the thickness of the plastic material is between 0.5 and 20 mm, and can effectively transmit electromagnetic waves of 1 to 300 GHz through specific formulations and processing processes.
The transmission of electromagnetic waves in the frequency range of 1 to 300GHz is achieved, especially in the radar frequency range of 76GHz to 81GHz, which significantly reduces fluctuation attenuation and is suitable for plastic materials covering radar detection systems and other equipment.
Smart Images

Figure 2025513771000001 
Figure 2025513771000002 
Figure 2025513771000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a plastic material and to moulded articles obtained therefrom. [Background technology]
[0002] The future of mobility will be increasingly focused on self-driving or autonomous vehicles. Self-driving cars use sensors to perceive their environment and navigate safely with little or no human intervention. The most common sensors are camera or radar-based systems. Radar technology has been used by automakers for years to assist with automatic cruise control and parking, and the same technology, combined with artificial intelligence, is expected to be used in driverless cars in the near future.
[0003] In a radar system, a transmitter generates electromagnetic waves at radio or microwave frequencies, which are transmitted by a transmitting antenna. The transmitted electromagnetic waves are reflected by radar-opaque objects and return to a receiver, providing information about the object's position and speed, allowing a vehicle to navigate safely within the environment.
[0004] The electromagnetic frequencies used in radar detection systems for autonomous driving are currently in the range of 76 GHz to 81 GHz. The use of lower or higher frequencies in the future cannot be excluded.
[0005] In vehicles, radar detection systems are commonly embedded in or shielded by exterior trim, most often mounted in the bumper. Because radar transmission through plastic materials can be hindered by undesirable transmission losses, any plastic material used to cover a radar detection system must be radar transparent, i.e., it must allow the incident electromagnetic waves to pass through the cover and cause minimal attenuation of the incident waves.
[0006] International Patent Application No. 2022 / 011131 discloses a pigment having an aspect ratio of at least 5 comprising a non-conductive composite material comprising a semiconductor and / or dielectric and a metal dispersed in the semiconductor and / or dielectric, which pigment can be applied as a coating on a plastic object.
[0007] International Patent Application No. 2021 / 030197 discloses a radar transparent TPO resin coated with a coating system comprising a film-forming resin and a flake pigment composition comprising at least 50% by weight of a radar transparent pigment and up to 50% by weight of a conductive pigment, the coating system transmitting at least 70% of electromagnetic radiation including frequencies between 1 and 100 GHz.
[0008] In this context, there is a need for a plastic material that allows the transmission of electromagnetic waves, including but not limited to radar frequencies, with minimal (if any) attenuation of the incident wave, and that is suitable for producing molded articles, particularly structural parts of molded articles, including but not limited to vehicle bumpers. Summary of the Invention
[0009] The present invention provides a molded article comprising a plastic material containing inorganic particles (M) containing 7.0% by weight or less of a metal element and at least 93.0% by weight of a polymer composition (A), the molded article having a thickness (d) of 0.5 to 20 mm and satisfying formula (I) when irradiated with electromagnetic waves having a frequency of 1 to 300 GHz.
number
[0010] The invention also provides the use of the moulded article for at least partially covering a device for emitting and / or receiving electromagnetic waves, preferably a radar detection system.
[0011] The invention also provides the use of a plastic material for optimizing the transmission and / or detection of electromagnetic waves with frequencies in the range 1-300 GHz through a molded article having a thickness d in the range 0.5-20 mm.
[0012] The plastic materials of the present disclosure and resulting molded articles allow for the transmission of electromagnetic waves, including but not limited to radar frequencies, while minimizing attenuation of the incident wave.
[0013] Thus, the article of the present disclosure may be a cover or housing for an electromagnetic source and / or detector, such as a radome. The article of the present disclosure may be a portion of a vehicle, such as a bumper, that shields an electromagnetic emitting and / or receiving device, such as a radar detection system.
[0014] The mechanical properties of the plastic material of the present invention are not substantially affected by the amount of inorganic particles (M) contained in the plastic material.
[0015] While multiple embodiments are disclosed, still other embodiments will become apparent to those skilled in the art from the following detailed description. As will be apparent, the specific embodiments disclosed herein can be modified in various obvious aspects without departing from the spirit and scope of the claims presented herein. Thus, the following detailed description should be regarded as illustrative in nature and not restrictive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In the context of this disclosure: -Percentages are expressed by weight unless otherwise specified.
[0017] -The total weight of a composition equals 100%, unless otherwise specified.
[0018] - The term "comprising" when referring to a polymer, plastic material, polymer composition, mixture or blend is to be interpreted as meaning "consisting essentially of or consisting of".
[0019] - The term "consisting essentially of" means that in addition to the essential components, other components may also be present in the polymer or polymer composition, mixture or blend, but the essential properties of the polymer or composition, mixture or blend are not substantially affected by their presence. Examples of components that, when present in normal amounts, do not substantially affect the properties of the polymer or polyolefin composition, mixture or blend are catalyst residues and processing aids.
[0020] - The term "copolymer" refers to a polymer resulting from the polymerization of at least two comonomers, i.e. the term "copolymer" includes bipolymers and terpolymers.
[0021] The plastic material preferably comprises 0.1-7.0 wt%, more preferably 0.1-4.0 wt%, even more preferably 0.5-4.0 wt% of inorganic particles (M) and 93.0-99.9 wt%, preferably 96.0-99.9 wt%, more preferably 96.0-99.5 wt% of a polymer composition (A), wherein the amounts of (M) and (A) are based on the total weight of the plastic material (total weight 100%).
[0022] In a preferred embodiment, the inorganic particles (M) are dispersed in the polymer composition (A), more preferably uniformly dispersed, the inorganic particles (M) being embedded in a matrix consisting of the polymer composition (A).
[0023] In the following the individual components of the plastic material are defined in more detail. The individual components may be present in the plastic material in any combination.
[0024] The polymer composition (A) preferably comprises up to 100% by weight of at least one polymer (a) selected from the group consisting of propylene polymers (a1), ethylene polymers (a2), polybutene-1 (a3), polystyrene (a4), acrylic polymers (a5), acrylonitrile butadiene styrene polymers (a6), acrylonitrile styrene acrylate polymers (a7), polyamides (a8), polyesters (a9), polyurethanes (a10), polycarbonates (a11) and mixtures thereof, the amount of polymer (a) being based on the weight of the polymer composition (A) (total weight 100%).
[0025] In one embodiment, the polymer composition (A) consists of at least one polymer (a).
[0026] The propylene polymer (a1) is preferably (a1.1) propylene homopolymers, (a1.2) Formula CH (A1) propylene copolymers with at least one olefin of =CHR, where R is hydrogen or linear or branched C2-C8 alkyl, preferably comprising up to 10.0% by weight, more preferably from 0.05% to 10.0% by weight, even more preferably from 0.1% to 8.0% by weight of units derived from an olefin, based on the weight of (a1.2); (a1.3) elastomeric propylene copolymers with at least one olefin of formula CH2=CHR, where R is hydrogen or a linear or branched C2-C8 alkyl, which preferably contain up to 85% by weight, more preferably from 5% to 85% by weight, even more preferably from 20% to 70% by weight, of units derived from an olefin, based on the weight of (a1.3), (a1.4) Recycled polypropylene (r-PP), which is a waste plastic material obtained from post-consumer waste and / or post-industrial waste; and (a1.5) mixtures thereof.
[0027] In one embodiment, the propylene copolymer (a1) is (1) 90% by weight or less, preferably 10% to 80% by weight, more preferably 15% to 70% by weight, of at least one propylene polymer selected from the group consisting of propylene homopolymers, propylene copolymers with at least one olefin of formula CH2=CHR (wherein R is hydrogen or linear or branched C2-C8 alkyl), which contain 10.0% by weight or less, preferably 0.05% to 10.0% by weight, more preferably 0.1% to 8.0% by weight, of units derived from an olefin, based on the weight of (1), and mixtures thereof; (2) an elastomeric propylene copolymer with at least 10% by weight, preferably 20% to 90% by weight, more preferably 30% to 85% by weight of at least one olefin of formula CH2=CHR, where R is hydrogen or a linear or branched C2-C8 alkyl, comprising up to 85% by weight, more preferably 20% to 85% by weight, even more preferably 25% to 75% by weight of olefin-derived units, based on the weight of (2); Here, the amounts of (1) and (2) are based on the total weight of (1)+(2).
[0028] In the propylene polymer (a1), the olefin is preferably selected from the group consisting of ethylene, butene-1, hexene-1, 4-methyl-1-pentene, octene-1 and combinations thereof, with ethylene and butene-1 being most preferred.
[0029] Propylene polymers (a1) are commercially available, for example, under the trade names Moplen, Hifax, Adstif, Clyrell, Softell, Hiflex, sold by LyondellBasell, and Vistamaxx, sold by Exxon Mobil. (商標) Also available in 6102.
[0030] The propylene polymers (a1) can be obtained by polymerizing the relevant monomers in the presence of metallocene or highly stereospecific Ziegler-Natta catalyst systems, which (1) a solid catalyst component comprising a magnesium halide support on which a Ti compound having at least one Ti-halogen bond is present, and a stereocontrolling internal donor; (2) optionally but preferably, an Al-containing cocatalyst; and (3) Optionally but preferably, includes an additional electron donor compound (external donor).
[0031] The solid catalyst component (1) preferably contains TiCl4 in an amount that ensures that 0.5 to 10% by weight of Ti is present relative to the total weight of the solid catalyst component (1).
[0032] The solid catalyst component (1) comprises at least one stereocontrolling internal electron donor compound selected from monodentate or bidentate organic Lewis bases, preferably selected from esters, ketones, amines, amides, carbamates, carbonates, ethers, nitriles, alkoxysilanes and combinations thereof.
[0033] Preferred donors are phthalate esters such as those described in European Patent Application Nos. 45977A2 and 395083A2, in particular diisobutyl phthalate, di-n-butyl phthalate, di-n-octyl phthalate, diphenyl phthalate, benzyl butyl phthalate, and combinations thereof.
[0034] The fatty acid esters may also be selected from malonic acid esters, such as those described in WO 98 / 056830, WO 98 / 056833, WO 98 / 056834, glutaric acid esters, such as those disclosed in WO 00 / 55215, and succinic acid esters, such as those disclosed in WO 00 / 63261.
[0035] A particular type of diester is one derived from the esterification of an aliphatic or aromatic diol, such as those described in International Patent Application No. 2010 / 078494 and US Patent Application No. P7,388,061.
[0036] In some embodiments, the internal donor is selected from 1,3-diethers such as those described in European Patent Application No. 361493, European Patent Application No. 728769, and International Patent Application No. 02 / 100904.
[0037] Internal donors can be used as internal donors, in particular the specific mixtures of aliphatic or aromatic mono- or dicarboxylic acid esters and 1,3-diethers disclosed in WO 07 / 57160 and WO 2011 / 061134.
[0038] The preferred magnesium halide supports are magnesium dihalides.
[0039] The amount of internal donor that remains fixed on the solid catalyst component (1) is between 5 and 20 mol % relative to the magnesium dihalide.
[0040] A preferred method for the preparation of the solid catalyst component (1) is described in European Patent Application No. 395083A2.
[0041] The preparation of the catalyst components by typical methods is described, for example, in European patent applications US Pat. No. 4,399,054, US Pat. No. 4,469,648, WO 98 / 44009 A1 and European patent application No. 395083 A2.
[0042] In some embodiments, the catalyst system comprises an Al-containing cocatalyst (2) preferably selected from Al-trialkyls selected from the group consisting of Al-triethyl, Al-triisobutyl, and Al-tri-n-butyl. The Al / Ti weight ratio in the catalyst system is 1-1000, preferably 20-800.
[0043] In an embodiment, the catalyst system comprises a further electron donor compound (3) (external electron donor) selected from among silicon compounds, ethers, esters, amines, heterocyclic compounds, in particular 2,2,6,6-tetramethylpiperidine, and ketones.
[0044] Preferred silicon compounds are selected from among methylcyclohexyldimethoxysilane (C-donor), dicyclopentyldimethoxysilane (D-donor) and mixtures thereof.
[0045] The polymerization process to obtain the propylene polymer (a1) may be carried out either in the liquid phase or in the gas phase, continuously or discontinuously.
[0046] Liquid phase polymerization can be carried out either in slurry, solution or bulk (liquid monomer), this latter technique being the most preferred and can be carried out in various types of reactors such as continuous stirred tank reactors, loop reactors or plug flow reactors.
[0047] The gas phase polymerization can be carried out in a fixed bed reactor, either fluidized or stirred, or in a multi-zone circulating reactor, as shown in European Patent Application No. 1012195.
[0048] The heterophasic propylene polymer may be obtained by melt blending components (1) and (2) or, preferably, by polymerizing the relevant monomers in at least two polymerization stages, where the second and each subsequent polymerization stage is carried out in the presence of the polymer produced and the catalyst used in the immediately preceding polymerization stage or in a multi-zone circulating reactor as disclosed in WO2011 / 144489 and WO2018 / 177701.
[0049] The reaction temperature is preferably in the range of 40° C. to 90° C., and the polymerization pressure is preferably 3.3 to 4.3 MPa in the case of a liquid phase process, and 0.5 to 3.0 MPa in the case of a gas phase process.
[0050] The ethylene polymer (a2) is preferably (a2.1) Thermoplastic ethylene polymers such as ultra-high molecular weight polyethylene (UHMWPE), high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and medium density polyethylene (MDPE); (a2.2) Formula CH2=CHR 1 (where R 1 is a linear or branched C1-C8 alkyl), which preferably comprises at least 20% by weight, more preferably 20% to 50% by weight, of units derived from an α-olefin, based on the weight of (a2.2); (a2.3) Recycled polyethylene (r-PE), which is a waste plastic material obtained from post-consumer waste and / or post-industrial waste; and (a2.4) mixtures thereof.
[0051] In the ethylene polymer (a2), the α-olefin is preferably selected from propylene, butene-1, hexene-1, octene-1 and combinations thereof.
[0052] Ethylene polymers (a2.1) are commercially available, for example under the trade names Alathon, Lucalen and Luflexen, sold by LyondellBasell, and can be prepared by known polymerization processes using Ziegler or Phillips catalysts, either in solution or in the gas phase.
[0053] Ethylene polymers (a2.2) are commercially available, for example, under the trade name Engage. (商標) 8100 or Engage (商標) 8150, sold by Dow®, can be obtained by known polymerization processes using metallocene-based catalyst systems.
[0054] The polybutene-1 (a3) is preferably a butene-1 homopolymer, ethylene and CH2=CHR 2 butene-1 copolymers (R 2 is methyl or a straight or branched C3 to C8 alkyl), and combinations thereof.
[0055] Ethylene and propylene are preferred comonomers in the butene-1 copolymer (a3). Preferably, ethylene and / or α-olefins are contained in the butene-1 copolymer (a3) in an amount ranging from 0.1% to 20%, based on the weight of the butene-1 copolymer (a3).
[0056] The butene-1 polymers (a3) are commercially available, for example under the trade name Koattro, sold by LyondellBasell, and can be prepared by known polymerization processes utilizing Ziegler-Natta or metallocene-based catalyst systems, typically using solution polymerization.
[0057] The polystyrene (a4) is preferably selected from thermoplastic homopolymers of styrene or α-methylstyrene (a4.1), saturated or unsaturated styrene or α-methylstyrene block copolymers (a4.2) (preferably comprising up to 30% by weight of polystyrene, more preferably comprising from 10% to 30% by weight, based on the weight of (a4.2)), recycled styrene block copolymers (r-SBC) (a4.3), which are waste plastic materials obtained from post-consumer and / or post-industrial waste, and mixtures thereof.
[0058] The saturated or unsaturated styrene or α-methylstyrene block copolymers (a4.2) are preferably selected from the group consisting of polystyrene-polybutadiene-polystyrene (SBS), polystyrene-poly(ethylene-butylene)-polystyrene (SEBS), polystyrene-poly(ethylene-propylene)-polystyrene (SEPS), polystyrene-polyisoprene-polystyrene (SIS), polystyrene-poly(isoprene-butadiene)-polystyrene (SIBS) and mixtures thereof.
[0059] Block copolymers of styrene and α-methylstyrene (a4.2) are produced by ionic polymerization of the related monomers and are sold by Kraton Polymers. TM It is sold under the trademark.
[0060] The acrylic polymer (a5) is preferably selected from the group consisting of poly(methacrylate) (PMA), poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate) (PEMA), poly(2-hydroxyethyl methacrylate) (poly-HEMA) and mixtures thereof.
[0061] The polyamide (a8) is preferably chosen from aliphatic polyamides, polyphthalamides, aromatic polyamides, polyamideimides, and mixtures thereof.
[0062] Among the aliphatic polyamides, nylon PA6 and nylon PA66 are most preferred.
[0063] Polyamides (a8) are commercially available and can be prepared by condensation polymerization processes well known in the art.
[0064] The polyester (a9) is preferably selected from the group consisting of polyethylene terephthalate (PET), glycol modified polyethylene terephthalate (PETG), polybutylene terephthalate (PBT), polylactic acid (PLA), polyglycolic acid (PGA), polycaprolactone (PCL) and mixtures thereof.
[0065] Polymer (a) optionally contains at least one additive selected from the group consisting of nucleating agents, antistatic agents, antioxidants, light stabilizers, slip agents, antacids, melt stabilizers, and combinations thereof in a conventional amount, preferably 5.0% by weight or less, more preferably 0.01% by weight to 5.0% by weight, based on the total weight of polymer (a) (total weight 100%).
[0066] In one embodiment, the polymer composition (A) comprises up to 50 wt. %, preferably 2-50 wt. %, of at least one further component (b) selected from the group consisting of fillers, pigments, flame retardants, compatibilizers, and combinations thereof, wherein the amount of (a) and (b) is based on the total weight of the polymer composition (100% total weight).
[0067] The filler is preferably a mineral filler, preferably selected from the group consisting of talc, mica, glass fibers, glass beads, carbon fibers, carbon black, natural fibers, carbon nanotubes, fullerenes, and combinations thereof.
[0068] The pigments and flame retardants are of the type used in the polyolefin field.
[0069] The compatibilizer is preferably a modified olefin polymer, preferably polypropylene and / or polyethylene, functionalized with a polar compound. The modified olefin polymer is selected from graft copolymers, block copolymers, and mixtures thereof. Preferably, the compatibilizer is a polyolefin functionalized with a compound selected from the group consisting of maleic anhydride, C1-C10 linear or branched dialkyl maleates, C1-C10 linear or branched dialkyl fumarates, itaconic anhydride, C1-C10 linear or branched itaconic acids, dialkyl esters, maleic acid, fumaric acid, itaconic acid, and mixtures thereof, more preferably selected from polyethylene, polypropylene, and mixtures thereof. In a preferred embodiment, the compatibilizer is maleic anhydride grafted polyethylene and / or polypropylene (MAH-g-PP and / or MAH-g-PE).
[0070] An example of a modified polyolefin suitable for use as a compatibilizer is the commercially available product Amplify® from Dow Chemical Company. (商標) TY, Exxelor of ExxonMobil Chemical Company (商標) Scona by Byk (Altana Group) (登録商標) TPPP, Bondyram of the Polyram Group (登録商標) , and Chemtura's Polybond (登録商標) and combinations thereof. The modified polymers can be produced by a functionalization process carried out in solution, in the solid state, or preferably in the melt, for example by reactive extrusion of the polymer in the presence of a grafting compound and a free radical initiator. The functionalization of polypropylene and / or polyethylene with maleic anhydride is described, for example, in European Patent Application No. 0572028A1.
[0071] Preferably, the polymer composition (A) comprises - 100% by weight or less, preferably 50% to 98% by weight, of the polymer (a) according to any one of the above embodiments, and -50% by weight or less, preferably 2% to 50% by weight, of a component (b) selected from the group consisting of fillers, pigments, flame retardants and combinations thereof; Here, the amounts of (a) and (b) are based on the total weight of polymer composition (A) (total weight 100%).
[0072] The metal element contained in the inorganic particles (M) is preferably selected from the group consisting of magnesium, calcium, strontium, barium, aluminum, titanium, vanadium, chromium, iron, copper, zinc, ruthenium, rhodium, palladium, silver, tin, platinum, gold, titanium, zirconium, alloys of these metals, and combinations thereof, and aluminum is particularly preferred.
[0073] The inorganic particles (M) preferably comprise or consist of metal particles, particles of inorganic compounds, and mixtures thereof.
[0074] The metal particles preferably consist of at least one of the metals mentioned above or at least one alloy thereof, preferably in the form of metal flakes, with aluminum flakes being particularly preferred.
[0075] The inorganic compounds are preferably selected from metal oxides and mixed metal oxides, such as Al2O3, TiO2, titanates and zirconates of the above metals, e.g., BaTiO3, Ca2ZrO4, ceramic particles containing the above metals, zeolites, and combinations thereof.
[0076] The inorganic particles (M) preferably have an average particle size D50 of 200 microns or less, more preferably 150 microns or less, and even more preferably 100 microns or less. In one embodiment, the lower limit of the average particle size is 1 micron for all the upper limits above.
[0077] Preferably, the inorganic particles (M) have a particle size of 0.2 microns or greater.
[0078] The plastic material is obtained by dry mixing, or preferably melt mixing, of the polymer composition (A) and the inorganic particles (M) in a conventional melt mixing device, preferably a twin-screw extruder, by feeding the device sequentially or simultaneously.
[0079] In one embodiment, the polyolefin composition (A) comprises a polymer (a) and a further component (b). The polymer (a) and the further component (b) can be dry mixed, or preferably mixed in a melt mixing device, before melt mixing the polyolefin composition (A) with the inorganic particles (M) to obtain a plastic material. Alternatively, the polymer (a), the further component (b) and the inorganic particles (M) can be dry mixed, or preferably fed separately into a melt mixing device to obtain a plastic material.
[0080] The presence of inorganic particles (M) in the plastic material in an amount of not more than 7% by weight has only a limited effect on the mechanical properties of the polymer composition (A), which do not differ significantly from the mechanical properties of the polymer composition (A) to which no inorganic particles (M) have been added.
[0081] The plastic materials of the present disclosure are suitable for forming molded articles, preferably structural parts of molded articles.
[0082] The moulded articles of the present disclosure are / are obtained by known methods for moulding plastic materials, preferably injection moulding.
[0083] In one embodiment, the molded article of the present disclosure is obtained or obtainable by molding, preferably injection molding, a plastic material as described above.
[0084] The molded article has a thickness d that satisfies the following formula (I) when irradiated with electromagnetic waves having a frequency of 1 to 300 GHz, preferably 70 to 130 GHz, and more preferably 76 to 81 GHz.
number
[0085] The thickness d of the molded product is in the range of 0.5 to 20 mm, preferably 0.5 to 15 mm, and more preferably 1 to 10 mm.
[0086] λ0 is a known value determined by the radiation irradiated to the molded article.
[0087] Preferably, m is an integer in the range of 1-20, preferably 1-16, more preferably 1-10, and even more preferably 1-6.
[0088] The molded articles of the present disclosure allow for the transmission of electromagnetic waves, including but not limited to radar frequencies, with minimal attenuation of the incident wave.
[0089] In a preferred embodiment, the molded article is a housing for a device that radiates and / or receives electromagnetic waves, such as a vehicle bumper, cover, or radome.
[0090] The molded articles of the present disclosure are suitable for at least partially, and preferably completely, covering devices that emit and / or receive electromagnetic waves, such as radar detection systems in autonomous vehicles.
[0091] The present disclosure therefore also refers to a device configured to emit and / or receive electromagnetic waves, at least partially, preferably completely, covered by a molded article as described above. In a preferred embodiment, the device is a radar detection system of an autonomous vehicle.
[0092] The invention also provides the use of a plastic material comprising not more than 7% by weight, preferably 0.05 to 7.0% by weight, of inorganic particles (M) containing metal elements and at least 93.0% by weight, preferably 93.0 to 99.95% by weight of a polymer composition (A), for optimizing the transmission of electromagnetic waves at a frequency in the range of 1 to 300 GHz through a moulded article having a thickness d of 0.5 to 20 mm, wherein the amounts of (A) and (M) are based on the weight of the plastic material (total weight 100%).
[0093] The use according to the present disclosure comprises the step of molding, preferably by injection molding, a plastic material into an article having a thickness d satisfying formula (I), where d, λ, ε r and the value of m is as defined above.
[0094] The present disclosure also provides a method for optimizing transmission of electromagnetic waves at frequencies in the range of 1 to 300 GHz through a molded article, the method comprising: Providing a plastic material comprising not more than -7% by weight, preferably 0.05 to 7.0% by weight, of inorganic particles (M) containing a metal element and at least 93.0% by weight, preferably 93.0 to 99.95% by weight of a polymer composition (A), the amounts of (A) and (M) being based on the weight (total weight 100%) of the plastic material; - Moulding the plastic material into an article having a thickness d in the range of 0.5-20 mm and satisfying the following formula:
number
[0095] Plastic material composition and d, λ0, ε rand the value of m is as above.
[0096] Optimizing the transmission of electromagnetic waves through the article optimizes the emission and / or detection of the electromagnetic waves by an emitting and / or detecting device shielded by the article, such as a radar detection system in an autonomous vehicle.
[0097] The features describing the subject matter of this disclosure are not closely related to each other, and thus a preferred range of one feature may be combined with a more preferred or less preferred range of another feature, regardless of the level of preference.
[0098] EXAMPLES
[0099] The following examples are for illustrative purposes only and are not intended to limit the scope of the disclosure in any way.
[0100] Characterization method
[0101] The following methods are used to determine the properties set forth in the description, claims, and examples.
[0102] Melt flow rate: measured according to DISO 1133 method (230°C, 2.16 Kg for thermoplastic polyolefins, 190°C, 2.16 Kg for compatibilizers).
[0103] Solubility in xylene at 25 °C: Place 2.5 g of polymer sample and 250 ml of xylene in a glass flask equipped with a refrigerator and a magnetic stirrer. The temperature is increased to 135 °C in 30 min. The resulting clear solution is stirred for another 30 min under reflux. The solution is cooled in two stages. In the first stage, the temperature is decreased to 100 °C in air with stirring for 10-15 min. In the second stage, the flask is transferred to a thermostatically controlled water bath at 25 °C and placed for 30 min. The temperature is decreased to 25 °C without stirring for the first 20 min and maintained at 25 °C with stirring for the last 10 min. The formed solid is filtered with fast-drying filter paper (e.g., Whatman filter paper grade 4 or 541). Pour 100 ml of the filtered solution (S1) into a pre-weighed aluminum container and heat to 140 °C on a heating plate under a nitrogen flow to evaporate off the solvent. The container is then placed in an oven at 80 °C under vacuum until the weight is constant. The amount of polymer that dissolves in xylene at 25 °C is then calculated. XS(I) and XS A The value is experimentally determined. The proportion of component (B) that dissolves in xylene at 25°C (XS B ) can be calculated using the following formula: XS = W(A) × (XS A ) + W(B) × (XS B ) where W(A) and W(B) are the relative amounts of components (A) and (B), respectively, and W(A)+W(B)=1.
[0104] C2 content in propylene-ethylene copolymer (II): 13 C NMR spectra were acquired on a Bruker AV-600 spectrometer equipped with a cryoprobe, operating at 160.91 MHz in Fourier transform mode at 120 °C. ββ Carbon Peak (CJ Carman, RA Harrington, and CE Wilkes, Macromolecules, 10, 3, 536 (1977)) was used as the internal reference at 2.8 ppm. Samples were dissolved in 1,1,2,2-tetrachloroethane-d2 at 120 °C to a concentration of 8% wt / v. Each spectrum was recorded using a 90° pulse, a 15 s delay between pulses, and 1 H- 13 The data were acquired using CPD to remove C bonds. 512 transients are stored in 32K data points using a 9000Hz spectral window. Spectral assignments, evaluation of triad distributions, and compositions Spectral assignments, evaluation of triad distributions, and compositions were performed according to the methodology proposed by Kakugo [M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules, 16, 4 , 1160 (1982)]. Because the amount of propylene inserted as an irregular unit was small, the ethylene content was calculated by the method described by Kakugo [M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules, 16, 4 , 1160 (1982)]. PPP=100T ββ / S PPE=100T βδ / S EPE=100T δδ / S PEP=100S ββ / S PEE=100S βδ / S EEE = 100 (0.25S γδ +0.5S δδ ) / S Here, S=T=T ββ +T βδ +T δδ +S ββ +S βδ +0.25S γδ +0.5S δδ
[0105] The molar contents of ethylene and propylene are calculated from the triplet using the following formula: [E]mol = EEE + PEE + PEP [P]mol = PPP + PPE + EPE
[0106] The weight percentage of ethylene content (E%wt) is calculated using the following formula:
number
[0107] The total ethylene content C2(tot) and the ethylene content C2(A) of component (A) are measured, and the ethylene content C2(B) of component (B) is calculated using the following formula. C2(tot)=W(A)×C2(A)+W(B)×C2(B) where W(A) and W(B) are the relative amounts of components (A) and (B) (W(A)+W(B)=1).
[0108] Flexural modulus: Measured according to ISO 178 / A:2019-04 on injection-molded specimens type 1 according to ISO 20753.
[0109] Relative permittivity ε r and attenuation: The dielectric constant is measured using a Radome Measurement System RMS-D-77 / 79G from perisens GmbH, which is used to perform free space transmission (S21) measurements of amplitude and phase and to determine the dielectric constant of materials in the frequency range 76-81 GHz. The instrument transmits radar waves of a given frequency band through a material sample. The attenuation of the signal is calculated from one measurement without the sample and one with the sample. The attenuation between both measurements and the thickness of the sample (measured with a Mitutoyo Digital Sheet Metal Micrometer IP65) are used to calculate the dielectric constant.
[0110] Particle size and particle size distribution: Measured by laser diffraction (eg using a Mastersizer Hydro 3000) (15 second test, stirring speed 3500 rpm).
[0111] raw materials:
[0112] HECO % of a propylene homopolymer (1) and 40% by weight of a propylene-ethylene copolymer (1) containing 68% by weight of ethylene, based on the weight of copolymer (b), the amounts of (a) and (b) being based on the total weight of HECO. HECO is a reaction mixture of components (a) and (b) obtained as described in Examples 1 and 2 of WO 2005 / 014715 A1.
[0113] talc :Jetfine® 3CA is sold by Imerys Performance Additives.
[0114] Inorganic particles (M): Perex A32-30LW, sold by Metaflake, is a pellet containing 30% by weight polyethylene wax and 70% by weight aluminum flake with an average particle size D50 of 32 microns.
[0115] Comparative Examples CE1 to CE2 and Example E3
[0116] The plastic material with the composition in Table 1 was compounded in a twin-screw extruder operated at 300 rpm, with a mass flow rate of 40 kg / h and a temperature of 220°C (zone 1 = 200°C, zone 2 = 210°C, zone 3 = zone 4 = zone 5 = zone 6). The article was obtained by molding the plastic material with the composition in Table 1 into a plate with a thickness of 2.42 mm using an injection molding machine with a clamping force of 1600 kN and a screw diameter of 50 mm. The extruder was operated under the following conditions: Melting temperature: 225℃; Mold temperature: 30℃; Average injection speed: 100mm / s; Cavity pressure switching point: 150bar; Holding pressure (hydraulic): 50bar; Dwell time: 30 seconds; Cooling time: 28 seconds.
[0117] The specimen is irradiated with a radar frequency of 77 GHz (vacuum wavelength λ0 corresponds to 3.89 mm) and equation (I) is satisfied with m = 2. The value of the relative dielectric constant εr was determined experimentally.
[0118] The composition of the plastic material and the test properties of the molded articles are shown in Table 1. [Table 1]
Claims
1. A molded article comprising a plastic material containing inorganic particles (M) containing 7% by weight or less of a metal element and 93.0% by weight or more of a polymer composition (A), the molded article having a thickness d in the range of 0.5 to 20 mm and satisfying formula (I) when irradiated with electromagnetic waves having a frequency of 1 to 300 GHz. [0010] (where: d is the thickness of the molded product, λ 0 is the vacuum wavelength corresponding to the frequency of the electromagnetic wave irradiated to the molded article, and ε r is the relative dielectric constant of the plastic material, m is a positive integer equal to or greater than 1, and the amounts of (A) and (M) are based on the total weight (100%) of the plastic material.
2. 2. The molded article according to claim 1, wherein the plastic material comprises 0.1-7.0 wt.%, more preferably 0.1-4.0 wt.%, more preferably 0.5-4.0 wt.% of the inorganic particles (M) and 93.0-99.9 wt.%, preferably 96.0-99.9 wt.%, more preferably 96.0-99.5 wt.% of the polymer composition (A), the amounts of (A) and (M) being based on the total weight (100%) of the plastic material.
3. 3. The molded article according to claim 1 or 2, wherein the polymer composition (A) comprises up to 100% by weight, preferably 50% to 98% by weight, of at least one polymer (a) selected from the group consisting of propylene polymers, ethylene polymers, polybutene-1, polystyrene, acrylic polymers, acrylonitrile butadiene styrene polymers, acrylonitrile styrene acrylate polymers, polyamides, polyesters, polyurethanes, polycarbonates, and mixtures thereof, the amount of the polymer (a) being based on the total weight (100%) of the polymer composition (A).
4. The molded article according to claim 3, wherein the polymer (a) is (1) 90% by weight or less, preferably 10% by weight to 80% by weight, more preferably 15% by weight to 70% by weight, - propylene homopolymer, -Formula CH 2 Propylene copolymers with at least one olefin of =CHR, where R is hydrogen or a linear or branched C2-C8 alkyl, containing up to 10.0 wt. %, preferably 0.05 wt. % to 10.0 wt. %, more preferably 0.1 wt. % to 8.0 wt. %, of units derived from an α-olefin, based on the weight of (1); and at least one propylene polymer selected from the group consisting of these mixtures, (2) at least 10% by weight, preferably 20% to 90% by weight, more preferably 30% to 85% by weight, of the formula CH (2) and an elastomeric propylene copolymer with at least one olefin of =CHR, where R is hydrogen or linear or branched C2-C8 alkyl, said elastomeric propylene copolymer comprising up to 85 wt. %, more preferably 20 wt. % to 85 wt. %, even more preferably 25 wt. % to 75 wt. %, of units derived from an α-olefin, based on the weight of (2), The amount of (1) and (2) is based on the total weight of (1) + (2).
5. 5. The molded article according to claim 1, wherein the polymer composition (A) further comprises up to 50% by weight, preferably from 2% to 50% by weight, of at least one additional component (b) selected from the group consisting of fillers, pigments, flame retardants, compatibilizers, and combinations thereof, the amount of component (b) being based on the total weight (100%) of the polymer composition (A).
6. The molded article according to any one of claims 1 to 5, wherein the metal element contained in the inorganic particles (M) is selected from the group consisting of magnesium, calcium, strontium, barium, aluminum, titanium, vanadium, chromium, iron, copper, zinc, ruthenium, rhodium, palladium, silver, tin, platinum, gold, titanium, zirconium, alloys of the metals, and combinations thereof.
7. The molded article according to any one of claims 1 to 6, wherein the inorganic particles (M) are metal flakes, preferably aluminium flakes.
8. The molded article according to any one of claims 1 to 7, wherein the inorganic particles (M) have an average particle size D50 of 200 microns or less, preferably 150 microns or less, more preferably 100 microns or less, as measured by a laser diffraction method.
9. The molded article according to any one of claims 1 to 8, wherein the molded article satisfies formula (I) when irradiated with electromagnetic waves having a frequency in the range of 70 to 130 GHz, preferably 76 to 81 GHz.
10. The molded article according to any one of claims 1 to 9, wherein m is in the range of 1 to 20, preferably 1 to 16, more preferably 1 to 10, and even more preferably 1 to 6.
11. The molded article according to any one of claims 1 to 10, wherein the thickness d of the molded article is in the range of 0.5 to 20 mm, preferably 0.5 to 15 mm, more preferably 1 to 10 mm.
12. The molded article according to any one of claims 1 to 11, wherein the molded article is a vehicle bumper, a cover, or a housing for a bus that emits and / or receives electromagnetic waves.
13. Use of a moulded article according to any one of claims 1 to 12 for at least partially covering a device which emits and / or receives electromagnetic waves, preferably a radar detection system of an autonomous vehicle.
14. Use of a plastic material according to any one of claims 1 to 11 for optimizing the transmission of electromagnetic waves with frequencies in the range 1 to 300 GHz through a moulded article with a thickness d of 0.5 to 20 mm.
15. 1. A method for optimizing the transmission of electromagnetic waves at frequencies in the range of 1-300 GHz through a molded article, comprising: - providing a plastic material according to any one of claims 1 to 11, and - forming an article having a thickness d in the range of 0.5 to 20 mm, the article satisfying the following formula: [0025] (where: d is the thickness of the molded part, λ 0 is the vacuum wavelength corresponding to the frequency of the electromagnetic wave irradiated to the molded product, the frequency being in the range of 1 to 300 GHz, ε r is the relative dielectric constant of the plastic material, m is a positive integer of 1 or more.
16. A device adapted to emit and / or receive electromagnetic waves, at least partially covered by an article according to any one of claims 1 to 12.
17. 20. The device of claim 16, which is a radar detection system for an autonomous vehicle.